2021
DOI: 10.1002/its2.84
|View full text |Cite
|
Sign up to set email alerts
|

Multienvironment evaluation of St. Augustinegrass breeding lines for turf performance via a mixed‐models approach

Abstract: St. Augustinegrass [Stenotaphrum secundatum (Walter) Kuntze] is a turfgrass extensively used in managed landscapes in Florida and throughout the southeastern United States. To develop cultivars with broad adaptation, it is necessary to understand the effect of genotype × environment interactions. The objective of this study was to estimate genetic parameters in St. Augustinegrass for coverage, turf quality (TQ), and turf color (TC) in a multienvironment trial across five locations in Florida (Arcadia, Hague, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…Heritability values for the traits evaluated in this study ranged from moderately low to high (.38 to .87). The estimate for TQ of .72 fell within the range of previously estimated values (Gouveia et al., 2021; Pereira et al., 2021) as did heritability estimates for WS and GLS (Atilano & Busey, 1983; Philley et al., 1998). Heritability can be utilized as an indicator of response to selection, and therefore improving the accuracy of heritability estimates can improve selection efficiency (Cassell, 2009; Schmidt et al., 2019).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Heritability values for the traits evaluated in this study ranged from moderately low to high (.38 to .87). The estimate for TQ of .72 fell within the range of previously estimated values (Gouveia et al., 2021; Pereira et al., 2021) as did heritability estimates for WS and GLS (Atilano & Busey, 1983; Philley et al., 1998). Heritability can be utilized as an indicator of response to selection, and therefore improving the accuracy of heritability estimates can improve selection efficiency (Cassell, 2009; Schmidt et al., 2019).…”
Section: Discussionsupporting
confidence: 86%
“…The GEI poses a challenge as plant breeders must either select for genotypes that perform well across environments, sacrificing potential genetic gain, or develop separate populations for each environment where performance is significantly different (Kang, 1997). While some studies have found GEI to influence St. Augustinegrass performance (Reynolds et al., 2009), others found that environment plays a minor role in genotype variability (Kimball et al., 2016; Pereira et al., 2021) and indicated the species has better stability across locations than other warm‐season turfgrass species (Gouveia et al., 2021). In this study, St. Augustinegrass performance was stable across locations as entry × location was an insignificant factor for all traits with the exception of EST.…”
Section: Discussionmentioning
confidence: 99%
“…A different study at target environments in Florida, showed that GEI was slightly more pronounced for TQ than for %GC in St. Augustinegrass. However, all locations were grouped in the same mega‐environment for TQ, whereas three mega‐environments were formed for %GC (Pereira et al., 2022). Time influences the gain from selection (Eberhart, 1970) and it is the most powerful parameter for increasing genetic gains in a breeding program (Cobb et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Since this initial observation, FSA1602 has been included in several trials. Results of a multi‐location turfgrass evaluation trial in Florida indicated that FSA1602 showed the best overall performance across the different traits analyzed (Pereira et al., 2021). For all the following experiments where data are reported for TQ, shade, or disease responses, the number of experimental entries may vary, but the comparison standard cultivars Floratam and Palmetto were included.…”
Section: Methodsmentioning
confidence: 99%